Biodegradability of some nitrogenous heterocyclic compounds and co-degradation with phenol by denitrifiers in anoxic sludge reactor - Wang, Zixing (Water science and technology : a journal of the International Association on Water Pollution Research, 2015)
Phenol and nitrogenous heterocyclic compounds (NHCs) are typical organic pollutants in coal gasification wastewater which are difficult to deal with. Unlike phenol, the stable molecular structure of NHCs make them nearly impossible to degrade under aerobic or anaerobic condition. In this paper, biodegradation of phenol and NHCs as carbon sources for denitrification was studied in a laboratory-scale anoxic reactor. Denitrifiers could degrade 490 mg/L phenol and 321.5 mg/L NO3(-)-N within 12 hours with removal efficiencies of 99.8% and 99.6%, respectively. The inhibition of pyridine on the microbes could be reduced by adding phenol into influent and the experimental results showed that pyridine could be degraded as the sole carbon source with the maximum organic loading rate of 4.38 mg/(g MLSS·h) (MLSS: mixed liquor suspended solids). When phenol was included as a growth substrate, the degradation performance of quinoline and pyrrole was improved due to co-degradation, and removal rate of NHCs increased according with increment of phenol in influent